Mobilising sustainable local government revenue in Ghana: modelling property rates and business taxes (Commonwealth Journal of Local Governance, 2015)
Property rates and business operating license fees constitute the major revenue sources for local government authorities. Accurate assessment of these revenues enhances the revenue base and effectiveness of their generation. Assessment of property rates and business operating license fees have been identified as one of the limiting factors that inhibit the revenue potential of local government authorities. Assessment must obey the principles of taxation such as efficiency, equity and fairness, adequacy, administrative feasibility and political acceptability. Over the years, the Sekondi-Takoradi Metropolitan Assembly (STMA) acknowledges that, it has had problems in ensuring equity and fairness in the assessment of property rates and business operating license fees. The paper reports on a computer modelling study carried out to introduce measure to ensure equity and fairness in assessing tax objects. A computer application has been developed with quantitative measures to evaluate and assess equity in tax assessment. A test run of the system has been successful and a pilot test is currently being implemented by STMA.